Peran Guru Dalam Mengembangkan Bakat dan Minat Peserta Didik Pada Mata Pelajaran Seni Budaya Dan Prakarya di Kelas IV A MIN 2 Kota Bengkulu - Diarti, Ilni (Yayasan Darusssalam Bengkulu, 2020)
The purpose of this study was to determine the role of teachers in developing student interest. The method used is a qualitative descriptive method. The results of the research regarding the Role of Teachers in Developing the Talents and Interests of Students in the Subject of Cultural Arts and Crafts in Class IV A MIN 2 Bengkulu City, it can be concluded that: The Role of Teachers in Developing the Talents and Interests of Students in Cultural Arts and Craft Subjects in Class IV A MIN 2 Bengkulu City is a very courageous teacher in developing students' talents and interests in the arts. This can be seen from the results of interviews and also the results of observations made by researchers that MIN 2 Bengkulu City does have teachers in the arts who can directly control how the talents and interests of students in the arts. Supporting factors include facilities and infrastructure in the learning process, the children themselves and their talents. Besides that, it also has inhibiting factors, including there are students who do not want to cooperate with their friends, there are also students who do not bring the tools that have been agreed upon, and there are also students who do not care less about working in groups.